Thermal properties of spent coffee ground biocomposite using epoxy resin matrix - Ismail; Aini, Quratul; Maulida, Cut Rizka; Mursal; Jalil, Zulkarnain; Md Fadzullah, Siti Hajar Sheikh (2023)
Coffee is one of the most popular drinks in the world. The use of coffee produces a large amount of coffee waste (spent coffee grounds). These spent coffee grounds contain cellulose and hemicellulose which have the potential to be used as a biocomposite material. The objective of this work was to study the thermal properties of spent coffee grounds biocomposite by using epoxy resin as a matrix. The particle size of spent coffee grounds was 20 and 40 mesh. The compositions of spent coffee grounds and epoxy resin for each particle size were 80/20, 85/15, 90/10, and 95/05 (vol.%). The biocomposite samples have been successfully fabricated by using the press method with 9 tons of load. The density and porosity of biocomposite samples have been examined. The thermal conductivity of biocomposite samples has been measured by a single-plate method. Differential scanning calorimetry and thermogravimetric analysis and have been also used to analyze the thermal properties of samples. The results found that the density of spent coffee grounds biocomposite was 0.605 – 0.789 g/cm3. The porosity of biocomposite samples was found to be in the range of 12 – 14%. TGA showed that the spent coffee grounds biocomposite had a stable weight up to 250 °C. Fast decomposition of the sample occurred after 250 °C. DSC spectra showed that there was an endothermic peak at 85 °C with the enthalpy change of 218 J/g. Another endothermic peak was also observed at 466 °C, related to the thermal depolymerization of the samples. The thermal conductivity of the spent coffee grounds biocomposite was 0.038 – 0.054 W/m K indicating that the spent coffee grounds biocomposite is quite suitable for thermal insulation. Composition spent coffee ground has a significant effect on the thermal and physical properties of biocomposite. This work found that the thermal conductivity of biocomposite correlates with its density and porosity.